Quixote's Ghost : the Right, the Liberati, and the Future of Social Policy. - Stoesz, David (Oxford University Press, 2005)
Quixote's Ghost, framed by the metaphor of a Romantic Left whose actions-like Don Quixote's obsession with chivalry-are out of synch with the present reality, will be of immense interest to students and academics alike. As one of the few books to chart this radical shift in social policy and its implications on the ground, it will be sure to challenge both the Right and the Left to craft a new approach to thinking about American social policy.